TANGGUNG JAWAB PELAKU USAHA ATAS IKLAN YANG MENYESATKAN - Netty Herawati (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2006)
Advertisement is the part of activity of marketing, what ought to is medium materialization of consumer rights specially the right to get information and the right to property. When advertised things oppose against common public grounds of rule code advertisement, for example advertised things disagree with the reality of hence emerging clear problems harm consumer side. Because existence of advertisement do not get out of the existence producer advertiser, service firm of advertisement advertisement bureau, and media, hence loss befalling third consumer of perpetrator component is effort that have to responsibility accounted-together. Concerning level of responsibility each perpetrator of effort that depended from store; level mistake of him.